AN ANALYSIS OF STUDENTS DIFFICULTY IN WRITING NARRATIVE TEXT IN CLASS X OF SMK NEGERI 1 KUTACANE ACADEMIC YEAR 2023/2024 - Putri Rizki; Wahyu Fatahillah; Meri Vancito (STKIP USMAN SAFRI KUTACANE, 2024)
A Thesis English Education Department the Faculty of Teachers Training and Education, stkip us Kutacane.The aim of the research was to find out the ability and difficulty in writing narrative text. Writing test and Questionnaire were used as the instrument of collecting data. The subject of this research were the X of SMK Negeri 1 Kutacane Academic Year 2023/2024. The method of this research was descriptive research. Writing test and questionnaire were used as the instrument of collecting data. the subject of this research were X of SMK Negeri 1 Kutacane .The result in this test was good and the mean score was (43.45). The second meeting the researcher explain again about questionnairebefore giving the questionnaire test, the result of the questionnaire of the students got (44.54) showed the students of X of SMK Negeri 1 Kutacane were easy to writing narrative text.